Pola Komunikasi Pelatih dengan Atlet dalam Membangun Kohesivitas Tim Karate Dojo Dengklok Perguruan BKC - Asyifa Mufida; Luluatu Nayiroh (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze and understand the communication events between the coach and athletes of the BKC Karate Team at Dojo Dengklok, as well as the forms of verbal and non-verbal communication within the team. The analysis is based on symbolic interaction theory and group convergence theory to examine group cohesiveness within the BKC Karate Team at Dojo Dengklok, Karawang Regency. The research was conducted using a qualitative method with an ethnographic study approach. The findings reveal that the cohesiveness of the BKC Karate Team at Dojo Dengklok is firmly established through rich symbolic interaction. Through symbols such as chants, belts, and rituals, as well as two-way communication and informal interactions among athletes, the team constructs shared meanings, a collective identity, and a sense of pride. This process also helps athletes understand their roles and shape their self-concepts. The BKC Karate Team at Dojo Dengklok demonstrates strong cohesiveness due to its effective management of internal conflicts. Minor conflicts, such as differences in technique or miscommunication, are resolved through mediation and deliberation led by the coach, as well as informal communication among athletes. This process allows the team to achieve symbolic convergence, transforming friction into a reinforcement of mutual understanding, trust, and team unity. The strong cohesiveness of the BKC Karate Team at Dojo Dengklok is formed through intense symbolic interaction and convergence abilities in facing challenges. This is evident from the shared meanings built through chants, belts, rituals, and both verbal and non-verbal communication. Moreover, informal interactions among athletes and the team's ability to support one another during economic hardships further strengthen their bonds and trust. These processes as a whole create a solid collective identity, a strong sense of belonging, and a unified purpose, making the team more than just a group of individuals.